Formulasi sabun padat dengan kandungan minyak atsiri Cymbopogon Nardus L. - Agusta, Herma Fanani; Wardani, Arief Kusuma; Hidayatullah, Farizqi Ramadhan (Borobudur Pharmacy Review, 2025)
Soap is a self-care product that plays an important role in maintaining body hygiene. The development of the cosmetic industry encourages innovation in soap formulations, one of which uses natural ingredients such as essential oils. Citronella oil is an agribusiness sector commodity with a good market share and high competitiveness. This study aims to develop a solid soap formulation containing Cymbopogon Nardus L. essential oil, which is known to have antimicrobial and antioxidant properties. Soap was made using a mixture of Virgin Coconut Oil and palm oil, NaOH with the addition of Cymbopogon Nardus L. essential oil and distilled water with varying concentrations. The basic physical and chemical properties of soap, such as organoleptic, pH and foam stability were evaluated with good soap parameters based on SNI 3532:1994. Based on the test results on the four formulas with the three parameters carried out, it can be concluded that the addition of citronella essential oil to the tested formulas strengthens the organoleptic characteristics of good solid soap. All formulas have pH values in the range that are slightly less safe for the skin (pH 10-13) as bath soap with SNI criteria (pH 9-11) and foam stability that tends to decrease during the 28 days of testing and outside the range of solid soap foam stability of 60-70% required by SNI 3532: 1994.